Nicotine induces alteration of H3K27 demethylase UTX in kidney cancer cell. (March 2014) - Guo, X; Li, X; Wang, Y; Tian, Z; Duan, X; Cai, Z
Cigarette smoking is one of the most important risk factors for kidney cancer, but the molecular mechanism is poorly understood. To examine the expression change of histone H3 on lysine 27 trimethylase (H3K27me3) demethylases ubiquitously transcribed TPR gene on the X chromosome (UTX) in kidney cancer cell line 786-O after nicotine treatment, quantitative real-time-polymerase chain reaction and western blotting analysis were carried out. These results showed that nicotine can increase UTX messenger RNA and protein levels and also decrease the content of H3K27me3. The decreased content of H3K27me3 may activate specific gene expression and lead to kidney cancer. Future investigation on nicotine induced UTX expression and its epigenetic effect would deepen our understanding on nicotine toxicity and carcinogenicity.